A V2I BASED APPROACH TO MULTICAST IN VEHICULAR NETWORKS - Tomar, Ravi; Sastry, Hanumat G; Prateek, Manish (Malaysian Journal of Computer Science, 2020)
The present research work proposes a novel approach for efficient information dissemination in Vehicular Networks using V2I based communication. This approach makes use of the V2I communication to establish the connectivity between the cloud server and the vehicle. The approach is focused on finding the utility of existing IoT protocols in the Vehicular Networks. The foundation of this work relies in the (Message Queue Telemetry Transport Protocol) MQTT protocol, IoT and IaaS. The paper presents the background technologies used in the work and propose the approach. The proposed approach has been experimentally tested and found significant results.